2018
DOI: 10.33549/physiolres.933848
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Targeting Human Endothelin-1 Receptors Reveal Different Conformational States in Cancer Cells

Abstract: The endothelin axis (endothelins and their receptors) is strongly involved in physiological and pathological processes. ET-1 plays a crucial role in particular in tumor diseases. Endothelin-1 receptors (ETA and ETB) are deregulated and overexpressed in several tumors such as melanoma and glioma. We studied the binding of 24 monoclonal antibodies directed against human ETB receptors (hETB) to different melanoma cell lines. Few of these mAbs bound to all the melanoma cell lines. One of them, rendomab B49, bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…28 Rendomab B49 is a murine IgG1kappa mAb that recognizes such an epitope near the N-terminal of the receptor. 25 We obtained the RB49 antibody conjugated to Alexa Fluor 488 and compared its binding to primary myeloma cells with the binding of a control IgG1k antibody. In 8 of the 10 (80%) tested primary MM samples, we could confirm the binding of RB49 to primary malignant plasma cells (results from one of these patients is illustrated in Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Rendomab B49 is a murine IgG1kappa mAb that recognizes such an epitope near the N-terminal of the receptor. 25 We obtained the RB49 antibody conjugated to Alexa Fluor 488 and compared its binding to primary myeloma cells with the binding of a control IgG1k antibody. In 8 of the 10 (80%) tested primary MM samples, we could confirm the binding of RB49 to primary malignant plasma cells (results from one of these patients is illustrated in Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
“…ET B is a G‐protein‐coupled receptor that changes its confirmation upon activation with new epitopes becoming exposed 28 . Rendomab B49 is a murine IgG1kappa mAb that recognizes such an epitope near the N‐terminal of the receptor 25 . We obtained the RB49 antibody conjugated to Alexa Fluor 488 and compared its binding to primary myeloma cells with the binding of a control IgG1k antibody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow Cytometry. We used the protocol of Herbet et al 30 Briefly, three cell lines were used to assess the apparent affinity of xiRA63 or xiRB49: Chinese hamster ovary wild-type (CHO-WT) cells and CHO cells were stably transfected with either human ET A (CHO-ET A ) or human ET B (CHO-ET B ). Apparent affinity was determined with a dilution range from 0.001 to 50 nM for xiRA63 and from 0.01 nM to 125 nM for xiRB49.…”
Section: Bioconjugatementioning
confidence: 99%
“…To circumvent this issue, two high-affinity antibodies�which do not compete with ET-1�named Rendomab A63 (RA63) and Rendomab B49 (RB49), directed, respectively, against ET A and ET B receptors have been patented. 8,9 We have recently demonstrated that a chimeric version of RA63 called xiRA63 could be randomly labeled with zirconium-89 ( 89 Zr, t 1/2 = 3. ing. 10 Likewise, a chimeric version of the latter, xiRB49, was modified with a cytotoxic molecule to obtain an antibody− drug conjugate showing a very high efficacy in treating ET B + melanoma with no notable side effects on mice (Herbet et al, in preparation).…”
Section: ■ Introductionmentioning
confidence: 99%